“ANALISIS PENGARUH KEPUASAN KERJA DAN IKLIM ETIKA TERHADAP KOMITMEN ORGANISASI DAN KINERJA KARYAWAN” (Studi Kasus pada Kantor Pusat PT Bank Rakyat Indonesia Tbk) - Gerry Suryosukmono; Slamet Widodo (Program Studi Magister Manajemen FE Unsri, 2020)
This research aims to testing and analyzing the influence between job satisfaction and ethical climate on employee job performance with organizational commitment as a mediating variable. The research of population was permanent employees of the seven divisions namely internal audit division, investment division, treasury division, international division, corporate secretary division, policy and human resources development divisions, and contract workers management division at the headquarters of PT Bank Rakyat Indonesia Tbk. Total sample amount to 150 people with convenience sampling method. The research method starting by running a pretest using Cronbach Alpha and factor analysis, continue by validity and reliability test using Confirmatory Factor Analysis. Next, these research followed by statistical description about respondents profile and test of hypothesis using SEM method. Results of study showed a significant effect between job satisfaction and organizational commitment, ethical climate influence on organizational commitment, job satisfaction with a direct relationship to performance, ethical climate with a direct relationship to the performance, and organizational commitment to employee performance. Besides that, significant effect also emerge from the influence of organizational commitment as mediating variable to the relationship of job satisfaction and work performance as well as to the ethical climate relationships and work performance.